ANALISIS KEAKTIFAN, KETERAMPILAN KOLABORATI, PRODUK NYATA DALAM MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA PEMBELAJARAN MATEMATIKA - Rizka Amalia; Muawwinatul Laili (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study was motivated by the fact that students continued to experience difficulties in understanding mathematics lessons, despite the teacher having implemented the Project-Based Learning (PjBL) model. The study aimed to describe the implementation of the PjBL model and to analyze student engagement, collaborative skills, and tangible products resulting from the model's application in mathematics lessons taught to Grade III students at SDN Sawohan II. A qualitative approach with a descriptive research design was employed. The research subjects consisted of one teacher and five Grade III students. Data were collected through observation, interviews, and documentation, and subsequently analyzed using the Miles and Huberman interactive model, which involves data reduction, data display, and conclusion drawing. Data validity was ensured through technique triangulation. The results indicate that the PjBL model was implemented through a process comprising project determination (via the introduction of surrounding objects), group planning of project completion steps, schedule creation with the teacher, project execution, report compilation and group presentations, and a concluding evaluation and reflection session. Regarding the engagement indicator, the PjBL model successfully fostered active participation and involvement among the majority of students in project design, discussions, and the completion of group tasks; however, this engagement was not yet universal across the class. Regarding collaborative skills, the Grade III students showed signs of development, and the tangible products generated by the students aligned with the intended learning objectives. ABSTRAK Penelitian ini dilatarbelakangi oleh peserta didik masih mengalami kesulitan dalam memahami pembelajaran matematika, meskipun guru telah menerapkan model pembelajaran Project Based Learning (PjBL) dalam proses pembelajaran. Penelitian ini bertujuan untuk mendeskripsikan penerapan model Project Based Learning serta menganalisis keaktifan, keterampilan kolaboratif, dan produk nyata peserta didik dalam penerapan model pembelajaran PjBL pada pembelajaran matematika yang diterapkan oleh guru dikelas III SDN Sawohan II. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Subjek penelitian terdiri atas seorang guru dan lima peserta didik kelas III. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis menggunakan model interaktif oleh Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Keabsahan data diperoleh melalui triangulasi teknik. Hasil penelitian menunjukkan bahwa penerapan model Project Based Learning telah dilaksanakan mulai dari penentuan proyek melalui pengenalan benda disekitar, perencanaan langkah-langkah penyelesaian proyek secara berkelompok, penyususnan jadwal bersama guru, penyelesaian proyek, penyusunan laporan serta presentasi kelompok di depan kelas, dan pelaksanaan evaluasi serta refleksi bersama pada akhir pembelajaran. Pada indikator keaktifan, penerapan model PjBL berhasil menumbuhkan keaktifan dan keterlibatan sebagian besar peserta didik dalam merancang proyek, berdiskusi, serta menyelesaikan tugas kelompok. Namun, keaktifan ini belum sepenuhnya menyeluruh. Pada indikator keterampilan kolaboratif kelas III sudah mulai berkembang, serta produk nyata yang dihasilkan peserta didik sesuai dengan tujuan pembelajaran yang diharapkan.